Stochastic stabilization of hybrid neural networks by periodically intermittent control based on discrete-time state observations. (May 2023) - Mao, Wei; You, Surong; Jiang, Yanan; Mao, Xuerong
Abstract: This paper is concerned with stabilization of hybrid neural networks by intermittent control based on continuous or discrete-time state observations. By means of exponential martingale inequality and the ergodic property of the Markov chain, we establish a sufficient stability criterion on hybrid neural networks by intermittent control based on continuous-time state observations. Meantime, by M-matrix theory and comparison method, we show that hybrid neural networks can be stabilized by intermittent control based on discrete-time state observations. Finally, two examples are presented to illustrate our theory.